Kepemimpinan Perempuan Muslimah Lintas Zaman: Potret Tokoh Ratu Balqis dan Sri Mulyani dalam Bingkai Islam - Nisa’, Khoirun (Maliki Interdisciplinary Journal, 2025)
This study explores the portrait of female leadership across time through two prominent figures: Queen Balqis from the Qur’anic narrative and Sri Mulyani Indrawati in the modern Indonesian context. Both represent different eras yet reflect strong, rational, and people-centered leadership. The study applies a qualitative-descriptive approach through library research. The analysis reveals that both leaders share similar leadership values such as openness to consultation, courage in strategic decision-making, and prioritization of public welfare. These findings indicate that female leadership in Islam is not contradictory to religious values but is instead rooted in both scriptural texts and real-world evidence.